High Voltage Electrical Discharges and Ultrasound-Assisted Extraction of Phenolics from Indigenous Fungus-Resistant Grape By-Product - Ante Lončarić; Antun Jozinović; Tihomir Kovač; Nebojša Kojić; Jurislav Babić; Drago Šubarić (Polish Journal of Food and Nutrition Sciences)
The possible use of high voltage electrical discharges (HVED) at different frequencies (20, 50, and 100 Hz) and ultrasound-assisted extraction (UAE) at different temperatures (20, 40, and 80°C) for the recovery of phenolics from indigenous fungus-resistant grape by-product was evaluated. All extractions were performed over the period of 5, 10, and 15 min and with methanol- and ethanol-based solvents. Grape pomace (the grape by-product) was collected during the preparation of grape jams. The main phenolics identified in grape pomace were anthocyanins, including malvidin, delphinidin, peonidin-3- O -glucoside, and cyanidin-3- O -glucoside. Beside anthocyanins, phenolic acids, flavan-3-ols, and flavonols were identified. The HVED-assisted extraction showed to be a superior extraction method for obtaining high yields of all analysed compounds. The highest amount of total phenolics (3023.57 mg GAE/100 g DM) was extracted from grape pomace, using 50% ( v/v ) ethanol and 60 kV/cm HVED at 100 Hz for 15 min. The antioxidant activity of the HVED extract was 2.17 mmol Trolox/g DM. The highest yield of the identified phenolics from grape pomace was obtained with electric field intensity of 60 kV/cm and total energy input of 22.27 kJ/kg, during the extraction.